2010
DOI: 10.1007/s10237-010-0258-y
|View full text |Cite
|
Sign up to set email alerts
|

Mean arterial pressure nonlinearity in an elastic circulatory system subjected to different hematocrits

Abstract: The level of hematocrit (Hct) is known to affect mean arterial pressure (MAP) by influencing blood viscosity. In the healthy population, an increase in Hct (and corresponding increase in viscosity) tends to raise MAP. However, data from a clinical study of type 2 diabetic patients indicate that this relationship is not universal. Instead, individuals in the lower levels of Hct range display a decrease in MAP for a given rise in Hct. After reaching a minimum, this trend is reversed, so that further increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In previous studies, we modeled the effects of a 10% increase in blood viscosity from baseline and found that it induced a significant decrease in peripheral vascular resistance (8), explaining the in vivo findings of Martini et al (27), who carried the same procedure in unanesthetized hamsters and mice. This effect could be present with 500-kDa dextran extreme hemodilution relative to 70-kDa dextran extreme hemodilution since blood viscosity increases from 2.1 to Fig.…”
Section: Discussionmentioning
confidence: 76%
“…In previous studies, we modeled the effects of a 10% increase in blood viscosity from baseline and found that it induced a significant decrease in peripheral vascular resistance (8), explaining the in vivo findings of Martini et al (27), who carried the same procedure in unanesthetized hamsters and mice. This effect could be present with 500-kDa dextran extreme hemodilution relative to 70-kDa dextran extreme hemodilution since blood viscosity increases from 2.1 to Fig.…”
Section: Discussionmentioning
confidence: 76%